Overview of qualitative and quantitative research methods in the field of library-material preservation - Krtalić, Maja; Hasenay, Damir (Qualitative and Quantitative Methods in Libraries; Vol 2 No 1 (2013): March 2013 Issue, 2017)
The aim of this paper is to give an overview of qualitative and quantitative methods used in the field of library-material preservation. Preservation of library materials is a diverse issue that can be researched from various standpoints. For instance, it is possible to explore development of theoretical approaches, preservation planning and management process, economic and legal aspects of preservation, necessary knowledge and competencies, different material properties and preservation methods, and impact of preservation on cultural and social issues. A variety of methods and techniques can be used for doing so, from experimental (instrumental) methods, statistical methods, and bibliometrics, on one hand, to content analyses, case studies, and unobtrusive measures, on the other. This work is based on the preservation-management model developed by the authors that comprises five key components: strategic and theoretical, economic and legal, educational, technical and operational, and cultural and social component. An overview of possible methods for exploring preservation issues—grouped according to these categories—will be given.